Historical reflections on the deterrent effect of the death penalty on capital crimes in South Africa: Lessons from 1917–1995 - Magobotiti, Chris (Scientia Militaria - South African Journal of Military Studies, 2022)
The death penalty was long practised in South Africa as one of the sentence options for capital crimes such as murder, rape, treason, terrorism, and robbery with aggravating circumstances. Its practice has a matching effort for its abolishment or restricted application. Reflecting on some specific historical periods of the practice of the death penalty in South Africa, the author sought to contextualise the article, namely to understand the socio-political experience and perception of the death penalty in order to gauge its current relevance. The goal of the study on which this article reports was to determine whether the death penalty had a deterrent effect on capital crimes in South Africa during the pre-1996 constitutional period. In order to achieve the goal of the deterrence of serious crimes by the death sentence in South Africa, the author discusses legislation, case law, execution patterns and deterrence literature in its context.